Seismicity and the State of Stress in the Dezful Embayment, Zagros Fold and Thrust Belt - Ali Yaghoubi; SeyedBijan Mahbaz; Maurice B. Dusseault; Yuri Leonenko (Geosciences, 2021)
This study focuses on determining the orientation and constraining the magnitude of present-day stresses in the Dezful Embayment in Iran’s Zagros Fold and Thrust Belt. Two datasets are used: the first includes petrophysical data from 25 wells (3 to 4 km deep), and the second contains 108 earthquake focal mechanisms, mostly occurring in blind active basement faults (5 to 20 km deep). Formal stress inversion analysis of the focal mechanisms demonstrates that there is currently a compressional stress state (<semantics>Aφ=2.0–2.2)</semantics> in the basement. The seismologically determined SHmax direction is 37° ± 10°, nearly perpendicular to the strike of most faults in the region. However, borehole geomechanics analysis using rock strength and drilling evidence leads to the counterintuitive result that the shallow state of stress is a normal/strike-slip regime. These results are consistent with the low seismicity level in the sedimentary cover in the Dezful Embayment, and may be evidence of stress decoupling due to the existence of salt layers. The stress state situation in the field was used to identify the optimally oriented fault planes and the fault friction coefficient. This finding also aligns with the prediction Coulomb faulting theory in that the N-S strike-slip basement Kazerun Fault System has an unfavorable orientation for slip in a reverse fault regime with an average SW-NE SHmax orientation. These results are useful for determining the origin of seismic activity in the basin and better assessing fault-associated seismic hazards in the area.